The Mandatory Program is Able to Read the Qur'an and Its Impact on the Morale of Unsyiah Students - Muchlinarwati Muchlinarwati; Muhammad Hamzah; Salami Salami; Sakdiah Sakdiah (Proceedings Series on Social Sciences & Humanities, 2023)
This research raised the topic of the mandatory program to be able to read the Quran and its impact on the morale of Unsyiah students. This research was conducted based on the fact that there are still a number of Unsyiah students who cannot read the Quran. In addition, there were also some obstacles for Unsyiah students in reading the Quran, it seems that they have not understood the correct makhraj letters and laws in tajwid. Therefore, the university of Shia Kuala (USK), organizes a program, namely UP3AI (the unit of development of a companion program for Islamic religious courses). This program, it can help students in reading the Quran. This program must be followed by all Unsyiah students as a condition of taking Islamic courses. The UP3AI program aims to form a generation that is Qur'ani and has a charitable character. This method uses qualitative and quantitative methods. The results of the student's research are that they have not been able to read the Quran properly. This program has not been implemented effectively, due to factors of lack of discipline, especially time, communication in teaching and learning is not good, and some mentors have not mastered the material and are said to be effective, namely the learning process between mentors and students has gone well, this can be seen in terms of the teaching and learning process, the time used is good, the methods used can be understood by students and techniques in teaching well. The success rate has not reached well due to the decline in the ability to not be able to read the Quran decreased quality of Quranic teaching in both mosques and Musalla, no stable teaching methods, limited hours of Quranic teaching, the elimination of teaching curricula, the influence of television shows and others. The implementation of the Quran reading program does not experience moral changes for students, but by practicing the Quran students will form good morals.